Pengelolaan Keuangan Sekolah Berbasis Good Governance di MTsN 1 Padang Pariaman - Muaddyl Akhyar; Hamdi Abdul Karim; Susanda Febriani; Ramadhoni Aulia Gusli (Program Studi Magister Pendidikan Agama Islam, 2024)
Financial management School financial management based on Good Governance is a very important approach to ensure the sustainability and improvement of the quality of education in schools, including in Indonesia, including in Indonesia. This study aims to analyze and evaluate the application of the principles of Good Governance in the management of financial management at MTsN 1 Padang Pariaman. This research uses a descriptive qualitative descriptive qualitative approach to examine school financial management based on Good Governance-based school financial management at MTsN 1 Padang Pariaman. The results of this study show that transparency in reporting and access to financial information at MTsN 1 Padang Pariaman still faces significant challenges. Key factors include the lack of effective information distribution mechanisms, limited access to information for stakeholders, as well as a lack of socialization on the importance of financial transparency. Financial reports are often incomplete and lacking in detail, coupled with the absence of standardized reporting standards, further complicating the situation. Nonetheless, efforts such as regular meetings with school committees and the use of information technology show potential for improvement. To improve transparency, it is necessary to increase the capacity of financial managers through intensive training, conduct regular and independent external audits and obtain clear regulatory support from the government. With these steps, it is expected that transparency in financial management at MTsN 1 Padang Pariaman can be improved. This is expected to increase public trust, encourage active stakeholder participation, and ensure more effective use of funds to improve the overall quality of education. Abstrak Pengelolaan keuangan sekolah berbasis Good Governance merupakan suatu pendekatan yang sangat penting untuk memastikan keberlanjutan dan peningkatan kualitas pendidikan di sekolah-sekolah, termasuk di Indonesia. Penelitian ini bertujuan untuk menganalisis dan mengevaluasi penerapan prinsip-prinsip Good Governance dalam pengelolaan keuangan di MTsN 1 Padang Pariaman. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk mengkaji pengelolaan keuangan sekolah berbasis Good Governance di MTsN 1 Padang Pariaman. Hasil penelitian ini menunjukkan bahwa transparansi dalam pelaporan dan akses informasi keuangan di MTsN 1 Padang Pariaman masih menghadapi tantangan signifikan. Faktor utama termasuk kurangnya mekanisme distribusi informasi yang efektif, keterbatasan akses informasi bagi pemangku kepentingan, serta kurangnya sosialisasi mengenai pentingnya transparansi keuangan. Laporan keuangan yang sering kali tidak lengkap dan kurang rinci, ditambah dengan ketiadaan standar pelaporan baku, semakin memperumit situasi ini. Meskipun demikian, upaya seperti rapat rutin dengan komite sekolah dan penggunaan teknologi informasi menunjukkan potensi untuk perbaikan. Demi meningkatkan transparansi, perlu ditingkatkan kapasitas pengelola keuangan melalui pelatihan intensif, dilakukan audit eksternal yang rutin dan independen, serta mendapatkan dukungan regulasi yang jelas dari pemerintah. Dengan langkah-langkah ini, diharapkan transparansi dalam pengelolaan keuangan di MTsN 1 Padang Pariaman dapat diperbaiki. Hal ini diharapkan dapat meningkatkan kepercayaan publik, mendorong partisipasi aktif pemangku kepentingan, dan memastikan penggunaan dana yang lebih efektif untuk peningkatan kualitas pendidikan secara keseluruhan.